Evaluation of English Textbooks for Class X Prescribed in BSER and CBSE Schools - Singh, Rajni; Choudhary, Sanjiv Kumar (INDIAN EDUCATIONAL REVIEW, 2015)
In India, the schools are affiliated to Central Board of Secondary Education (CBSE), Indian Certificate of Secondary Education (ICSE) or State Boards of Secondary Education. Every state has its own state board of education with its own syllabus. Variation is found in the syllabi of English at secondary school level of different boards. That is why the textbooks prescribed for the schools affiliated to different boards are also different. This study traced the appropriacy of English textbooks prescribed for class X by CBSE and the Board of Secondary Education Rajasthan, Ajmer (BSER). Data were gathered using checklist from the respondents and were analysed using descriptive and inferential statistics. The findings show that there are various aspects of textbooks with which teachers are quite satisfied. However, there are areas which need modification or to be supplemented by additional materials.